2018
DOI: 10.1029/2018gl079972
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Weak Intrinsic Magnetic Field on Atmospheric Escape From Mars

Abstract: The magnetization of a planet significantly changes the nature of atmospheric escape, and the question of whether a planetary field shields atmosphere from erosion by the solar wind or not remains open. Ion escape processes from Mars are investigated under two hypothetical conditions, namely, no intrinsic magnetic field and weak intrinsic dipole field cases under present solar wind conditions based on multispecies magnetohydrodynamics simulations. The existence of a weak dipole field results in an enhancement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 28 publications
8
52
3
Order By: Relevance
“…Recent MAVEN observations found that the crustal magnetic field induces the escape of molecular ions from the low‐altitude ionosphere (Inui et al, ). Sakai et al () investigated the effects of an intrinsic magnetic field on ion loss from present Mars based on the same simulation model as that used in this study. Their study concluded that the existence of a weak intrinsic magnetic field increases the ion loss, particularly the molecular ion loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent MAVEN observations found that the crustal magnetic field induces the escape of molecular ions from the low‐altitude ionosphere (Inui et al, ). Sakai et al () investigated the effects of an intrinsic magnetic field on ion loss from present Mars based on the same simulation model as that used in this study. Their study concluded that the existence of a weak intrinsic magnetic field increases the ion loss, particularly the molecular ion loss.…”
Section: Discussionmentioning
confidence: 99%
“…Strangeway () revealed the correlation between the ionospheric outflow and the downward Poynting flux based on measurements from the Fast Auroral Snapshot Small Explorer. MHD simulations of present Mars with a weak dipole field also indicated that the existence of a weak intrinsic global dipole magnetic field increases ion loss (Sakai et al, ). Some hybrid simulation studies reported the same effects of a weak intrinsic magnetic field on ion loss, while they also showed that the existence of a strong intrinsic magnetic field reduces ion loss (Egan et al, ; Kallio & Barabash, ).…”
Section: Introductionmentioning
confidence: 99%
“…Ion escape from the Earth's polar caps is strongly driven by Poynting flux and electron precipitation in the cusps (Strangeway et al, ) and correlates with solar wind‐driven geomagnetic activity, which can push O + escape rates up to ∼10 26 s −1 during severe storms (Slapak et al, ). In the simulations by Sakai et al () the introduction of a weak Martian dipole (100 nT equator surface) enhanced the heavy ion escape rate by 25 % ; however, the screening properties of a dipole may increase with higher magnetic moment values Cnossen et al (). The total effect of the presence of a dipole on ion escape is therefore likely a function of its strength in relation to the intensity of the solar wind, which may have been much weaker at 4.1 Ga (Wood et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The latter is dependent on the ambipolar electric field that stems from the difference in the velocities of ions and electrons (Axford, 1968); electrons typically move faster, thus causing charge separation and inducing an electric field, which accelerates the ions and permits their escape (Schunk and Nagy, 2009). The polar wind may become increasingly important for weak dipole magnetic fields with B p ∼ 10 −7 T for Mars-like exoplanets (Sakai et al, 2018); see also Lingam (2019).…”
Section: A Planetary Magnetospheresmentioning
confidence: 99%